Behavioural Determinants of Secondary Agriculture-based Entrepreneurs in Assam (Indian Journal of Extension Education, 2025)
Rural India still struggles with income gaps. Secondary agriculture serves as a strategic path to promote efficient rural entrepreneurship. The study was conducted in 2024 in Assam’s Dhubri district employing a mixed-method research design that examined variations in entrepreneurial attributes across secondary agricultural enterprises, based on data from 100 respondents representing five enterprises. Entrepreneurial behaviour showed positive correlations with factors like education, income, investment, media use, aspiration, motivation, gratification, and values, and a negative correlation with age. Multiple regression analysis explained 72.8 per cent of entrepreneurial behaviour (adjusted R² = 0.645). Using principal component analyses (PCA) and Varimax rotation, 23 entrepreneurial attributes were grouped and renamed into seven factors. The strategic policy advocacy to enhance entrepreneurs’ holistic development should prioritize these key attributes of secondary agriculture-based entrepreneurs to improve their entrepreneurial behaviour.